MiR‐455‐3p regulates early chondrogenic differentiation via inhibiting Runx2. Issue 23 (20th October 2015) - Zhang, Zhiqi; Hou, Changhe; Meng, Fangang; Zhao, Xiaoyi; Zhang, Ziji; Huang, Guangxin; Chen, Weishen; Fu, Ming; Liao, Weiming
Abstract : The expression of miR‐455‐3p has been shown to be up‐regulated in chondrogenesis of mesenchymal stem cell, but its role in different stages during chondrogenesis remains unknown. Here, we show that miR‐455‐3p is increased in ATDC5 cells from 0 d to 21 d, but rapidly decreases at 28 d, and a similar expression kinetic is detected in the development of mouse embryos. We show that miR‐455‐3p functions as an activator for early chondrogenic differentiation, most likely by inhibiting the expression of Runt‐related transcription factor 2 (Runx2) as indicated by luciferase reporter assays. In conclusion, miR‐455‐3p may activate early chondrogenesis by directly targeting Runx2. Abstract : MiR‐455‐3p is a chondrogenic related microRNA. MiR‐455‐3p is shown to function as an activator in early chondrogenesis by inhibiting Runx2. MiR‐455‐3p may activate early chondrogenesis by directly targeting Runx2.